Combination of ozonation and absorption through membrane contactor to remove ammonia from waste water - Sutrasno Kartohardjono; Milasari Herdiana Putri; Setijo Bismo (Jurnal Teknik Kimia Indonesia, 2012)
Ammonia in waste water is a major pollutant produced in industrial and agricultural waste water. Ammonia is often removed by conventional technologies such as pack tower aeration, biological treatment or adsorption as ammonium ion onto zeolites. In many cases, conventional methods are very costly and inefficient, and therefore, there is a need for an alternative separation technique for more efficient removal of ammonia from waste waters. The aim of this study is to investigate the performance of the combination of ozonation and absorption through membrane processes to remove ammonia from wastewater using natural hot spring water (NHSW) as absorbent. Experimental results show that operating variables such as time and pH of absorbent solution are found to remarkably influence the removal process efficiency. Based on experimental results ozonation can improve ammonia removal efficiency through the hollow fiber membrane contactor. Ammonia removal efficiencies and overall mass transfer coefficients increase with decreasing pH of absorbent solution. Keywords: ammonia, mass transfer, membrane, ozonation, removal efficiencyAbstrak Amonia di dalam air limbah merupakan polutan utama yang berasal dari air limbah industri dan pertanian. Amonia kebanyak disisihkan dengan teknologi konvensional seperti aerasi di menara isian, pengolahan secara biologi atau penyerapan sebagai ion amonium pada zeolit. Dalam banyak hal, metode konvensional sangat mahal dan kurang efisien, sehingga diperlukan teknik separasi alternatif untuk proses penyisihan amonia dari air limbah yang lebih efisien. Tujuan dari studi ini adalah untuk menyelidiki kinerja kombinasi proses ozonasi dan proses absorbsi melalui membran untuk menyisihkan amonia dari air limbah menggunakan absorben berbahan dasar air dari sumber air panas. Hasil eksperimen memperlihatkan bahwa variabel operasi, seperti waktu dan pH larutan penyerap, sangat mempengaruhi efisiensi proses penyisihan amonia. Berdasarkan hasil eksperimen, ozonasi dapat meningkatkan efisiensi penyisihan ammonia melalui kontaktor membran serat berlubang. Efisiensi penyisihan amonia dan koefisien perpindahan massa keseluruhan naik dengan turunnya pH larutan penyerap.Kata kunci: amonia, perpindahan massa, membran, ozonasi, efisiensi penyisihan